Systems controls are needed to reduce mistaken tests for hemophagocytic lymphohistiocytosis, results of a prospective quality-improvement cohort study. Issue 26 (2nd July 2021) - Safi, Salahuddin; Shanbhag, Satish; Hambley, Bryan C.; Merrill, Samuel A.
Abstract : Abstract: Medical diagnosis and therapy often rely on laboratory testing. We observed mistaken testing in evaluations for hemophagocytic lymphohistiocytosis (HLH) that led to delays and adverse outcomes. Physicians were mistakenly ordering interleukin-2 and quantitative natural killer cell flow cytometry, rather than soluble interleukin 2 receptor (sIL2R) or qualitative natural killer functional tests in the evaluation of patients suspected to have HLH. We initiated a prospective quality improvement project to reduce mistaken testing, reduce delays in correct testing due to mistaken ordering, and improve HLH evaluations. This consisted of provider education, developing an evaluation algorithm, and ultimately required systems interventions such as pop-ups and removal of the mistaken tests from the electronic ordering catalog. Active education reduced mistaken testing significantly in HLH evaluations from baseline (73.3% vs 33.3%, P = .003, relative risk reduction (RRR) 54.5%), but failed to meet the pre-specified RRR cutoff for success (70%). Education alone did not significantly reduce the proportion of HLH evaluations with delays in sIL2R testing (23.3% vs 7.4%, P = .096). Mistaken testing increased after the active intervention ended (33.3% vs 43.5%, P = .390, with RRR 40.7% from baseline. Mistaken test removal was successful: mistaken testing dropped to 0% ( P < .001, RRR 100%), saved 14, 235 yearly, eliminated delays in sIL2R testing from mistaken testing (23.3% vs 0%, P = .008), and expedited sIL2R testing after admission for HLH symptoms (14.6 days vs 3.8 days, P = .0012). These data show systems controls are highly effective in quality improvement while education has moderate efficacy.